2009
DOI: 10.1103/physreva.79.013812
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear harmonic generation and devices in doubly resonant Kerr cavities

Abstract: We describe a theoretical analysis of the nonlinear dynamics of third-harmonic generation ͑ → 3͒ via Kerr ͑ ͑3͒ ͒ nonlinearities in a resonant cavity with resonances at both and 3. Such a doubly resonant cavity greatly reduces the required power for efficient harmonic generation, by a factor of ϳV / Q 2 , where V is the modal volume and Q is the lifetime, and can even exhibit 100% harmonic conversion efficiency at a critical input power. However, we show that it also exhibits a rich variety of nonlinear dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(86 citation statements)
references
References 45 publications
9
75
0
2
Order By: Relevance
“…The frequency mismatch at which this bifurcation occurs is proportional to P m , so that, as P m → 0, the regime over which there exist high-efficiency steady states reduces to a single fixed point occurring at cp = 0. Beyond this bifurcation point, the system enters a limit-cycle regime (shaded regions) characterized by periodic modulations of the output signal in time [37,38,72]. Interestingly, we find that the average efficiency of the limit cycles (dashed lines)…”
Section: Frequency Mismatchmentioning
confidence: 88%
See 3 more Smart Citations
“…The frequency mismatch at which this bifurcation occurs is proportional to P m , so that, as P m → 0, the regime over which there exist high-efficiency steady states reduces to a single fixed point occurring at cp = 0. Beyond this bifurcation point, the system enters a limit-cycle regime (shaded regions) characterized by periodic modulations of the output signal in time [37,38,72]. Interestingly, we find that the average efficiency of the limit cycles (dashed lines)…”
Section: Frequency Mismatchmentioning
confidence: 88%
“…Multistability complicates matters since, depending on the initial conditions, the system can fall into different stable solutions and in particular, simply turning on the source at the critical input power may result in an undesirable low-efficiency solution. One well-known technique that allows such a system to lock into the desired high-efficiency solutions is to superimpose a gradual exponential turn-on of the pump with a Gaussian pulse of larger amplitude [37]. We found that a single Gaussian pulse with a peak power of 4P crit 0 and a temporal width ∼τ m , depicted in the right inset of Fig.…”
Section: -4mentioning
confidence: 94%
See 2 more Smart Citations
“…Since nonlinear optical effects are generally weak in bulk materials, we focus on nanostructured resonant systems with strong effective nonlinear interactions 10,12 . Such systems are susceptible to universal descriptions based on the coupled-mode theory framework 13,14 , which we exploit to investigate the ways in which nonlinearities can enable interesting/designable radiative effects. In particular, we show that self-phase modulation (SPM) and two-photon absorption (TPA) effects lead to strong modifications of their emissivity, including thermal broadening and non-Lorentzian, asymmetric lineshapes.…”
Section: Introductionmentioning
confidence: 99%